Domain wall depinning from FM/AFM interface defects by spin-polarized current - F. A. L. Andrade; F. V. S. Diniz; S. M. S. B. Martins Jr.; L. L. Oliveira; Ana L. Dantas; A. S. Carriço (AIP Advances, 2022)
We report a theoretical investigation of the impact of spin-transfer torque on magnetic head-to-head domain walls of Fe and Ni80Fe20 (Permalloy PyTM) nanowires exchange coupled to a two-sublattice uniaxial antiferromagnetic substrate. Our results indicate that provided the interface exchange interaction is large enough, the domain walls pin to interface defects consisting of steps perpendicular to the easy antiferromagnetic axis, separating terraces with opposite effective interface exchange fields. We also found that the dipolar and interface energies lead to narrow V-shaped domain walls and that the spin-transfer torque effects are restricted to the domain wall. Depinning walls from the step defect at the interface require polarized spin current densities of the order of 107 A/cm2 for both materials.